PERANAN USTADZ/USTADZAH DALAM MEMBINA AKHLAK SANTRI TPQ AL-HIKMAH DESA NGEPUNG KECAMATAN LENGKONG KABUPATEN NGANJUK - Moh Bahrulloh Sabana; Juli Amalia Nasucha (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2026)
Character development is an effort or measure taken by an educator toward their students with the aim of improving and advancing their ethics, so that students may possess good character and honorable habits. This study focuses on the role of Ustadz/Ustadzah in shaping the morality of students at the Al-Hikmah TPQ in Ngepung Village, Lengkong Subdistrict, Nganjuk Regency. This article describes the role of the ustadz and ustadzah at TPQ Al-Hikmah in Ngepung Village, Lengkong Subdistrict, Nganjuk Regency, in fostering the moral character of the students. This research is a qualitative study that employs a descriptive analytical approach. Data collection was conducted through observation, interviews, and document review. The informants who participated in this study consisted of five individuals: a religious leader, one male religious teacher, and three female religious teachers. The results of the study indicate that the students exhibit positive moral behavior, such as greeting others upon entering a room, shaking hands with the ustadz or ustadzah, performing wudu and praying before studying, dressing neatly, speaking politely, and asking permission before leaving the classroom. Efforts to foster moral character undertaken by the ustadz and ustadzah include guiding students in prayer before studying, encouraging them to perform wudu before studying, teaching them to bring their study materials, supervising students during the learning process, offering advice, and studying the ta’lim textbook. Factors that support moral development include Islamic norms, support from parents and the community, and the students’ enthusiasm for participating in TPQ activities. However, there are also factors that hinder character development, such as the students’ desire to play constantly, a lack of communication and tolerance from some parents, limited classroom facilities and teaching staff, and the students’ very young age